Karakteristik Butir Soal Setara AKM Numerasi Berbasis Jotform untuk Peserta Didik SMP - Mulyani, Adela; Masriyah; Sari, Yurizka Melia (Universitas Negeri Surabaya, 2025)
The low percentage of numeracy proficiency among junior high school students, as reported in the 2024 Indonesian Education Report, emphasizes the importance of high-quality numeracy questions equivalent to the Minimum Competency Assessment as effective practice materials to enhance students' numeracy skills. This study aims to analyze the characteristics of numeracy questions equivalent to the Minimum Competency Assessment delivered through the Jotform platform for junior high school students. The items are developed as online practice materials aimed at familiarizing students with solving numeracy problems in accordance with the standards of the national competency assessment. This research is an exploratory study using a quantitative approach. The primary data were collected from the result of 20 numeracy items distributed through Jotform to 27 students enrolled in the eighth grade of a privacy secondary school located in Surabaya. Four analyses were conducted to examine the item characteristics: validity, reliability, difficulty index, and discrimination index. Findings indicate that the average validity of the items falls within the moderate level, the reliability in categorized as high, the average difficulty index is also in the moderate range-suggesting the items are effective for evaluating students’ numeracy skill-and the average discrimination index demonstrates an excellent classification. In light of the results, the questions are considered appropriate for use in online numeracy practice.